1. The problem statement, all variables and given/known data consider the difference equation x(n+2)-0.3679x(n+1)+0.3679x(n)=0.3679u(n+1)+u(n) where u(n) is the input and given by u(n)=0 n<0 u(0)=1 u(1)=0.2142 u(2)=-0.2142 u(n)=0 n=3,4,5....... determine the output x(n) 3. The attempt at a solution let A=0.3679 and B=0.3642 i took z transform for both sides so it became. z^2 x(z)-z^2x(0)-zx(1)-A[zx(z)-zx(0)]+Ax(z)=A[zu(z)-zu(0)]+Bu(z) x(z)[z^2-Az+A]+x(0)[Az-z^2]-zx(1)=A[zu(z)-zu(0)]+Bu(z) x(z)[z^2-Az+A]=A[zu(z)-zu(0)]+Bu(z)-x(0)[Az-z^2]+zx(1) then what can i do? also how can i make use of u(1)=0.2142 u(2)=-0.2142 i am too confused and need help.